Waktu Pembayaran Fidiah Puasa (Studi Komparasi Mazhab Hanafi dan Mazhab Syafii): The Timing of Fidiah Payment for Fasting (A Comparative Study of the Hanafi and Shafi'i Schools of Thought) (AL-FIKRAH: Jurnal Kajian Islam, 2025)
This study aims to examine the differences in views between the Hanafi and Shafi'i schools regarding the timing of fidiah payment for missed fasting, and to analyze the comparative perspectives on the timing of fidiah payment in these two schools. The background of this study arises from the practice of Indonesian Muslims, who generally follow the Shafi'i school but often pay fidiah unsystematically, even before the cause of the obligation occurs. This research employs a descriptive qualitative design using the library research method, with a normative legal approach and a comparative approach. The findings indicate that the Hanafi school permits fidiah to be paid daily, in a lump sum at the end of Ramadan, after Ramadan, or even at the beginning of Ramadan, provided there is confidence that the excuse will persist for the entire month, and it may also be paid daily. Conversely, the Shafi'i school requires that fidiah be paid only after its cause occurs that is, after missing the fast on a specific day and prohibits advance payment based on the legal maxim that a ruling cannot precede its cause. This difference reflects the methodological approaches of the respective schools: the flexibility of the Hanafi school and the precision in timing of the Shafi'i school. The results of this study are expected to contribute to the development of Islamic law, serve as a reference for academic circles, and provide guidance and information for the wider community.